Hydrology and Hydraulic Analysis of Nasiri Flash Flood Disaster Event on the 1st August 2012 - Imam Syarif Hidayatulloh; Adam Pamudji Rahardjo; Bambang Agus Kironoto (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Nasiri lays in the Luhu village, Huamual district, West Seram Regency, Maluku province. Nasiri experienced in flash flood on August 1st, 2012 which had never happened before. There was no rainfall station and water level recorder at that time. It is rather difficult to find out the cause and yet Nasiri River was only 8 meters wide. The research started with identifying base flow, soil characteristics, learning flood video record, routing the river reach, finding the nearest rainfall station, and also interviewing some peoples there. Field data area was complemented with satellite radars. AutoCAD 2007, IFAS 2.0.1.2, Geostudio 2004, ArcGIS 10.2, HEC-HMS 4.2.1, and HEC-RAS 5.0.3 were used to perform simulations of the natural river with and without precipitation calibration, and also with and without landslide dam in the river. HEC-RAS was subject to perform 2 (two) dimensional flood routing. The result was fairly satisfying. Nasiri watershed was experiencing in flash flood caused by 2 (two) landslide dams which collapsed in 2 (two) different times. The first landslide dam was 7.55 meters high which collapsed at 09:52 (UTC+9) with 83.58 m3/s of peak discharge. The second landslide dam was 8.91 meters high which collapsed at 14:24 (UTC+9) with 54.16 m3/s of peak discharge